EVALUATION OF THE EFFICACY OF ALCHORNEA CORDIFOLIA MÜLL. ARG., AGERATUM CONYZOIDES LINN AND EUPHORBIA HIRTA LINN PLANT EXTRACTS AGAINST VIRULENT ASPERGILLUS SPECIES (FULafia Journal of Science and Technology, 2018)
Antifungal activities of the aqueous and ethanolic extracts of Alchonea cordifolia Müll. Arg., Ageratum conyzoides Linn. and Euphorbia hirta Linn. plants were evaluated both in vitro and in vivo against Aspergillus fumigatus, A. niger, A terreus, A, tamarii Kita. and A. ustus; these are mostly implicated in plant and animal fungal diseases. Thin layer chromatography was used to separate and identify the plant components and confirmation of phytochemical screening. Antifungal potential of the extracts were evaluated quantitativelyin vitro using well diffusion method and in vivo by studying the survival rate of Drosophila melanogaster challenged with the test standard isolates and compared with controls. The percentage yields of aqueous extracts were greater than that of ethanolic. Both extracts showed a potentially good antifungal activity, however aqueous extract had more activity. The activities increased with increasing concentration. Maximum antifungal activity was shown by aqueous of A. conyzoides against A. niger and A. ustus with the average inhibition of 20 mm each while the least activity were extracts of A. cordifolia against A. fumigatus at the concentration of 800mg/ml with 7mm zones of inhibition. Itraconazole (positive control) at 16.667m/ml, ranged from 15±0.13mm to 20±0.13mm with MIC values from 2.630mg/ml to 6.761 mg/ml. The MIC values of extracts ranged from 50mg/ml to 794mg/ml. The phytochemical screening revealed the presence of some phytochemicals. The activities of the plant extracts against the standard organisms in vivo did not correlate well with the in vitro.
Keywords: A. cordifolia; A. conyzoides; phytochemical screening; Antifungal potential; Drosophila melanogaster